Editorial Volume 6 Issue 2 - Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2012)
This issue of AABFJ has several finance articles from a New Zealand context. Koerniadi and Tourani-Rad (2012) examine board independence and firm value. Goslin, Chai and Gunasekarage (2012) consider whether financial statement information can be used to earn abnormal returns. Finally, Yahanpath and Koh (2012) look at bond covenants and the extent to which they offer protection to bondholders.
Keywords: Editorial; AABFJ